End-to-End Detector Optimization with Diffusion Models: A Case Study in Sampling Calorimeters - Kylian Schmidt; Krishna Nikhil Kota; Jan Kieseler; Andrea De Vita; Markus Klute; Abhishek; Max Aehle; Muhammad Awais; Alessandro Breccia; Riccardo Carroccio; Long Chen; Tommaso Dorigo; et al. (Particles)
Recent advances in machine learning have opened new avenues for optimizing detector designs in high-energy physics, where the complex interplay of geometry, materials, and physics processes has traditionally posed a significant challenge. In this work, we introduce the end-to-end. AI Detector Optimization framework (AIDO), which leverages a diffusion model as a surrogate for the full simulation and reconstruction chain, enabling gradient-based design exploration in both continuous and discrete parameter spaces. Although this framework is applicable to a broad range of detectors, we illustrate its power using the specific example of a sampling calorimeter, focusing on charged pions and photons as representative incident particles. Our results demonstrate that the diffusion model effectively captures critical performance metrics for calorimeter design, guiding the automatic search for a layer arrangement and material composition that align with known calorimeter principles. The success of this proof-of-concept study provides a foundation for the future applications of end-to-end optimization to more complex detector systems, offering a promising path toward systematically exploring the vast design space in next-generation experiments.